ANALISIS STRATEGI KOMUNIKASI PEMASARAN TERHADAP KEPUASAN KONSUMEN PADA INDOMARET KECAMATAN RENGEL - Haya Nur Safa’atin; Ulfatur Rhohmah; Ria Rahmawati; Abdullah Hanif Jalal (Mount Hope Management International Journal, 2024)
This research analyzes the marketing communication strategy carried out by Indomaret in Punggulrejo Village, Rengel District, and its impact on customer satisfaction. Through a qualitative approach, data was obtained through interviews, observations, and document analysis. The results show that Indomaret successfully uses various communication channels, such as leaflets, Instagram, and barcode-based applications to reach consumers. Weekly changing sales promotions and direct sales through the cashier increase consumer satisfaction and loyalty. Despite challenges related to stock availability and mispricing, these strategies are effective in increasing brand awareness and a satisfying shopping experience. This research provides insights for the development of more effective marketing strategies in the face of retail business competition.